Livro dentro do livro: relações intertextuais e dialógicas em O grifo de abdera, de Lourenço Mutarelli - Kaczuroski, Thiago (2021)
This research seeks to investigate how the dialogical and intertextual relations occur in the novel O Grifo de Abdera, by São Paulo’s writer Lourenço Mutarelli (1964 -), a special work for having a comic book inserted in its main narrative. Based on the concepts of “dialogue” and “intertertextuality”, developed from the writings of the Russian philosopher Mikhail Bakhtin and his commentators in the West, we try to show how the concept and its interpretations have been spread and reinterpreted over time. From texts by Julia Kristeva, responsible for the dissemination of his work in Europe and the Americas; Paulo Bezerra, its main translator in Brazil; Beth Brait, one of the main specialists in the Bakhtinian work in the country; and the critic José Luiz Fiorin, we bring to light the controversies about the terms and their understanding. Starting from the reading of the novel, we trace a theoretical path that goes through authors such as Roland Barthes and his “album” concept as opposed to the “book”, T.S. Eliot and Albert Camus to arrive at the definition of the differences between dialogical relations (which take place from the text, but with elements outside the text) and intertextual relations (which take place from the text and which have strictly textual elements). When analyzing the work in question, we draw a typology of the different relationships found in a literary work and how this type of relationship is present in any literary narrative in relation to its peers and its historical and social context